Efficacy of FEIBA for acute bleeding and surgical haemostasis in haemophilia A patients with inhibitors: A multicentre registry in Turkey - Zülfikar, B.; Aydogan, G.; Salcioglu, Z.; Oner, A.F.; Kavakli, K.; Gursel, T.; Biner, Betul (My University, 2012)
Long used in established industrialized nations to treat patients with haemophilia and inhibitors, factor eight inhibitor bypassing activity (FEIBA) has, in recent years, been introduced into more geographically diverse settings. Data are needed on how successfully FEIBA therapy has been implemented in new regions. To determine the efficacy and safety of FEIBA for the treatment of acute bleeding and surgical haemostasis in a newly industrialized country. A multicentre registry of haemophilia A patients with inhibitors receiving FEIBA treatment was established in Turkey. With a standardized case report form, data were collected retrospectively on: patient demographics; characteristics of acute bleeding episodes and surgical interventions; FEIBA regimen; and treatment outcomes. Thirty-seven patients received a total of 112 FEIBA treatment courses, 90 for acute bleeding and 22 for surgical haemostasis. The median FEIBA dose per infusion for acute bleeding was 50IUkg -1, and for surgery was 100IUkg -1. For both acute joint and muscle/soft tissue bleeding and in surgery, haemostasis was attained in a median of two FEIBA infusions. FEIBA was judged effective in 92% of treatment courses for acute bleeding, with a 95% confidence interval (CI) of 85-97%. Rates of haemostatic efficacy did not differ significantly between anatomical sites of acute bleeding. The haemostatic efficacy rate of FEIBA in surgery was 86% (CI, 65-97%). No thromboembolic complications or other adverse events occurred during any treatment course. FEIBA has been successfully integrated into clinical practice in Turkey, with rates of haemostatic efficacy comparable to those reported in countries with a longer history of FEIBA usage. © 2011 Blackwell Publishing Ltd.
Keywords: Acute haemorrhage; Blood coagulation factor inhibitors; Factor VIII inhibitor bypass activity; Haemophilia A; Haemostatic efficacy; Surgical haemostasis